Specific learning difficulties manifestation in children with average intelligence and children with intellectual disabilities - Chichevska Jovanova, Natasha; Rashikj Canevska, Olivera; Karovska Ristovska, Aleksandra; Dimitrova Radojichikj, Daniela; Cekovska Vesna (Faculty of Philosophy, Skopje, 2018)
Introduction: Children with specific learning difficulties represent a significant number of the population. It is necessary though to make a distinction between learning difficulties in children with typical development and problems in learning in children due to their intellectual disabilities. Aim: The goal of this research is to present the manifestation of the specific learning difficulties in 48 children with average intellectual abilities and 32 children with intellectual disability. Methods: In the sample, 80 children in total were covered, on the age between 5 and 10 years (62 boys and 18 girls). A descriptive and clinical method of work was applied, as well as the techniques: content analyses and testing which was consisted by a battery of tests. Results: From the total number of identified children with learning difficulties, a large part manifest difficulties in mastering reading techniques, males being the predominant group, and more than half having an inappropriate behavior regarding their age. Conclusions: Regarding the social importance of learning, it is mandatory that the problems and issues related to learning should be socially prioritized. Family oriented early intervention services which will be resource based and culturally sensitive should be introduced on a national level.
Манифестација на специфични тешкотии во учењето кај деца со просечна интелигенција и деца со интелектуална попреченост
Keywords: specific learning disabilities; associated disorders; hand preference; intellectual disabilities